Medien der Geschichte: antikes Griechenland und Rom - Dally, Ortwin; Hölscher, Tonio (De Gruyter, 2013)
Our understanding of past societies is shaped by the media that constitute their cultural practices. The essays in this volume examine the specific forms by which Ancient Greek and Roman civilizations presented themselves in literature and inscriptions, sculpture and monuments, habitats and rituals. They explore the question of how the ways that media construct historical realities come together to form an overall concept of history. O. Dally,DAI Berlin; T. Hölscher, Ruprecht-Karls-Universität Heidelberg;S. Muth, HU Berlin; R.-M. Schneider,LMU München.
Description based upon print version of record
Keywords: Electronic books; Konferenzschrift -- 2010 -- Heidelberg; Geschichte; Quelle; Antike